Reductive Cytochrome P450 Reactions and Their Potential Role in Bioremediation - Behrendorff, James B. Y. H. (Frontiers in Microbiology, 2021)
Cytochrome P450 enzymes, or P450s, are haem monooxygenases renowned for their ability to insert one atom from molecular oxygen into an exceptionally broad range of substrates while reducing the other atom to water. Under hypoxic conditions P450s can also perform reductive reactions, contributing electrons to substrates that present little or no opportunity for oxidation. These reductions drive dehalogenations and denitrations of a range of environmentally persistent compounds including halogenated hydrocarbons and organic nitramide explosives. P450-mediated reductive dehalogenations were first discovered in the context of human pharmacology but have since been observed in P450s from a variety of organisms. Additionally, reductive denitrification of synthetic explosives by P450 enzymes has been discovered in bacteria that inhabit contaminated soils. This review will examine the distribution of P450-mediated reductive dehalogenations and denitrations in nature and discuss the potential for using P450s and synthetic biology to develop new biological reagents for bioremediation.